Analysis Of Science Concepts On Physical And Chemical Changes In The Mamaq Tradition Of The Sasak Ethnic Group - Fahmi Firdaus; Maulidatin Nanisfi; Siti Diniah; X Zardht Alex Hidayat; Yayuk Andayani; Aliefman Hakim; Saprizal Hadisaputra (Indonesian Journal of Educational Innovation, 2025)
Mamaq is a traditional practice passed down through generations of the Sasak tribe. Analysing the idea of science in relation to the physical and chemical alterations in the Sasak tribe’s mamaq tradition is the goal of this study. This research uses a qualitative approach with a descriptive research type to explore in-depth knowledge about the mamaq tradition of the Sasak tribe. Direct observation and interviews were used to get data from community leaders and cultural figures, as well as secondary data from various relevant written sources. The analysis results found several scientific concepts in the mamaq tradition related to physical and chemical changes, including: 1) The betel nut that is cut, there is a physical change in the structure of the betel nut from a round shape to small pieces. 2) The betel leaves that are folded, there is a change in the shape of the leaves into a square fold. 3) There is a transition from a solid to a liquid texture in the ground mamaq substance. 4) The combination of mamaq components, where the chemicals in the finely ground substances generate a red colour. Thus, it may be said that the physical and chemical changes in the Sasak tribe’s mamaq tradition contain a scientific concept